Efek Variasi Campuran Solvent-Varnish dan Suhu Pengeringan terhadap Karakteristik Pelapis - Sopiyan; Muhammad Iqbal; Ferry Budhi Susetyo (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
Painting is a process to make a thin layer of paint over an object. Factors to beautify the results of painting on the vehicle body are given a layer of varnish. To produce a quality varnish coating, it is necessary to pay attention to the ratio between the varnish-solvent used and the drying method used. This study aims to determine the mixture of varnish - solvent (1:0,1 and 1:0,2) with a drying temperature method of 40°C, 60°C, and 80°C on gloss, thickness, and adhesion to the motor vehicle body. The lower the oven temperature, the higher the gloss and the thicker the coating. The best adhesion at the oven temperature of 40ºC and 60ºC on all varnish-solvent compositions. The higher of the solvent mixture would result glossier and less thickness of the layer form.